PENINGKATAN PENGETAHUAN TENTANG STUNTING PADA IBU KEK DAN FAKTOR RESIKO TUMBUH KEMBANG FLAT FOOT PADA ANAK - Syarifah, Syarifah (Community Services and Social Work Bulletin, 2023)
Pregnant women who experience chronic energy deficiency (KEK) can put their baby at risk of stunting. Stunting is a child's developmental disorder caused by a lack of nutritional intake, infection, or inadequate stimulation. Flat feet in children are a consequence of various factors such as obesity or heredity. It can be classified as a physiological or pathological disorder. Foot problems such as flat feet or flat feet are one of the main causes of various other complaints that are often underestimated. The implementation method used in this Community Service activity is presentation, discussion, and mentoring. It was concluded that increasing stunting knowledge for SEZ pregnant women and flatfoot risk factors in children meant that the learning process which lasted for two sessions with 20 participants of pregnant women with SEZs could be carried out smoothly and well.